2015
DOI: 10.1016/j.ydbio.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

DAAM1 and DAAM2 are co-required for myocardial maturation and sarcomere assembly

Abstract: Wnt ligands regulate heart morphogenesis but the underlying mechanisms remain unclear. Two Formin-related proteins, DAAM1 and 2, were previously found to bind the Wnt effector Disheveled. Here, since DAAM1 and 2 nucleate actin and mediate Wnt-induced cytoskeletal changes, a floxed-allele of Daam1 was used to disrupt its function specifically in the myocardium and investigate Wnt-associated pathways. Homozygous Daam1 conditional knockout (CKO) mice were viable but had misshapen hearts and poor cardiac function.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 84 publications
(136 reference statements)
2
47
1
Order By: Relevance
“…including sarcomeric organization and cell size control (42), probably via cooperation with formins. Daam1, another major cardiac formin (41), has been reported to be required for myocardial maturation and sarcomere assembly (7,43). In contrast to the localization of Fhod3 at the central region of sarcomeres, mouse Daam1 in the cardiomyocytes mainly localizes to the cell membrane not in a sarcomeric pattern (7), suggesting that Daam1 and Fhod3 regulate cardiac actin dynamics in a different manner.…”
Section: Role Of Fhod3 In the Neonatal And Adult Heartmentioning
confidence: 99%
“…including sarcomeric organization and cell size control (42), probably via cooperation with formins. Daam1, another major cardiac formin (41), has been reported to be required for myocardial maturation and sarcomere assembly (7,43). In contrast to the localization of Fhod3 at the central region of sarcomeres, mouse Daam1 in the cardiomyocytes mainly localizes to the cell membrane not in a sarcomeric pattern (7), suggesting that Daam1 and Fhod3 regulate cardiac actin dynamics in a different manner.…”
Section: Role Of Fhod3 In the Neonatal And Adult Heartmentioning
confidence: 99%
“…Loss of DAAM-family formins significantly perturbs sarcomere organization in mammalian and insect muscle (Molnar et al, 2014;Ajima et al, 2015), while worm DAAM-1 appears dispensable (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…Similar, but lesser, defects were also observed in heart and larval body wall muscles partially deficient for DAAM (Molnar et al, 2014). In mice, conditional DAAM1 knock out led to non-compaction cardiomyopathy with misshapen hearts and poor cardiac function, and simultaneous knock out of DAAM1 and DAAM2 led to even stronger myopathy, with severely reduced cardiac function and disrupted sarcomere structure (Ajima et al, 2015). An RNA interference (RNAi)-based study in neonatal mouse cardiomyocytes confirmed the importance of DAAM1 for myofibril organization, and also implicated FMNL-family formins FMNL1 and FMNL2, as well as the DIAPH-family formin DIAPH3 (Rosado et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Factors DAAM 1 and 2 appear at the Z-disc before actin filament assembly and recruit the critical factor, profilin, for actin polymerization [45][46][47]. DAAM1/2 mouse knockout models display disrupted cardiac sarcomere assembly and intercalated disc structures [48] and DAAM Drosophila mutants demonstrate disorganized sarcomeres with reduced thin filament numbers [49]. Since DAAM1/2 are members of the formin family of proteins, DAAM1/2 possess formin homology domains 1 and 2 (FH1 and FH2, respectively).…”
Section: Thin Filament Assembly In the Sarcomerementioning
confidence: 99%
“…A second model for actin recycling relies on reusing factors that were involved in sarcomere assembly. DAAM1/2, a formin protein, is localized to the Z-disc, where it recruits profilin and synthesizes F-actin during sarcomere assembly [48,51,55,143]. FHOD3, the debated formin discussed in thin filament assembly, is required for sarcomere maintenance by regulating actin dynamics and a lack of formin proteins increases the cytoplasmic concentration of G-actin [51,143,144].…”
Section: Dynamic Actin Turnovermentioning
confidence: 99%